Effect of dam construction on spawning activity of Yellow River carp (Cyprinus carpio) in the lower Yellow River - Bao, Hexin; Zhang, Shanghong; Tang, Caihong; Yang, Xiyan (Frontiers in Earth Science, 2022)
The construction of water conservancy projects not only brings benefits such as flood control and disaster reduction, but also has many effects on the habitat and reproduction of local aquatic organisms. Taking the reach from Xuzhuang Station to Gaocun Station in the lower Yellow River as an example, this paper discusses the effect of the Xiaolangdi Reservoir on the habitat of Yellow River carp(cypinusy carpio). By constructing a two-dimensional hydrodynamic model, coupled with a habitat suitability model of the spawning ground of Yellow River carp, the weighted usable area (WUA) of Yellow River carp habitat was calculated, and the spatial distribution of the habitat suitability index (HSI) in the reach was analyzed to evaluate habitat quality before and after the construction of the Xiaolangdi Reservoir. The results showed that the Xiaolangdi Reservoir had a negative effect on the habitat of Yellow River carp, resulting in the reduction of the spatial distribution of HSI, a decrease in WUA by 45.53%, and a decrease in habitat quality. The construction of the Xiaolangdi Reservoir reduced or even eliminated flow pulses in the downstream reach, but had little effect on the suitability index of water depth and velocity. However, the suitability index of water level rise was significantly reduced, which is not conducive to the spawning activities of aquatic organisms and has a negative effect on habitat. The results of this study will provide a reference for ecological restoration in this region.